Improving oral health through dental fluoride varnish application in a primary care paediatric practice. Issue 2 (31st May 2019) - Sudhanthar, Sathyanarayan; Lapinski, Jillian; Turner, Jane; Gold, Jonathan; Sigal, Yakov; Thakur, Kripa; Napolova, Olga; Stiffler, Michael
Abstract : Dental caries affect 97% of people during their lifetime. A total of 59% of children aged 12–19 will have at least one documented cavity. The American Academy of Pediatrics recommends fluoridated toothpaste to all children starting at tooth eruption, regardless of caries risk. Besides, fluoride varnish is recommended for all children every 3–6 months from tooth emergence until they have a permanent dental home. This project aimed to increase oral fluoride varnish application for children starting at 6 months or the time of tooth eruption up to 3 years of age by at least 50% over 18 months. The stakeholders identified were physicians, nurses, medical assistants and the health information team. We obtained baseline data about oral health screening and fluoride varnish from both the clinic sites. The quality improvement (QI) project was based on Plan-Do-Study-Act (PDSA) cycles with a 6-month gap in-between the three cycles. For the first cycle, all medical staff members participated in 2-hour knowledge and skills training on dental caries and current recommendations on fluoride varnish. PDSA cycle 2 involved having automatic reminders for providers in electronic medical records. PDSA cycle 3 planned to have automatic fluoride orders for the recommended age groups. The QI team analysed the results after every 6 months, and improvements were made based on the input from data and medical staff. The number of patients who had fluoride varnish applied increased from 14% (n=50) to 55% at the end of PDSA cycle 3. Administration of the varnish did not affect the flow of the patients in busy primary care practice. The rate of improvement was across all the age groups, providers and in both clinical sites. It is possible to adhere to the oral fluoride varnish guidelines in a busy primary care practice, which may help benefit young children who are at risk for caries.